PEMAKZULAN INDRA MUCHLIS ADNAN DARI JABATAN KETUA DEWAN PIMPINAN DAERAH (DPD) I PARTAI GOLONGAN KARYA (GOLKAR) RIAU - Zulkarnain "; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study back ground occurrence Impeachment Indra Muchlis Adnan from department heads the District Leadership Council I The party Golongan Karya Riau, where the department Indra Muchlis Adnan as the District Leadership Council I Golkar party Riau has not completed a five year term of office as may be set forth in Articles of Incorporation and Bylaws Golkar party, which traveled up mechanism should implement Extraordinary Provincial Consultation.Impeachment or more commonly known is the removal of an impeachment from office before the end of the department, usually due to an action that violates the values and norms which have been arranged in an institution or agency organization. This study was performed in DPD I Golkar party Riau Province to research the type of descriptive and qualitative approach and Technique of data collection using an interview guide, documentation and supported by theories that correspond to the theoretical research as a political Party, Leadership, Impeachment, and Management of conflict.Results from this study is that there are several factors that cause happens Impeachment against Indra Adnan Muchlis departmental ketua DPD I Golkar party Riau both internally as coordination problems and interests of the elite and the DPD I eksternnal as political moment at the close of the election district head Riau Province and interest elit